2016
DOI: 10.1038/onc.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

The C/EBPδ protein is stabilized by estrogen receptor α activity, inhibits SNAI2 expression and associates with good prognosis in breast cancer

Abstract: Hypoxia and inflammatory cytokines like interleukin-6 (IL6) are strongly linked to cancer progression, and signal in part through the transcription factor Ccaat/enhancer binding protein δ (C/EBPδ, CEBPD), which has been shown to promote mesenchymal features and malignant progression of glioblastoma. Here we report a different role for C/EBPδ in breast cancer. We found that the C/EBPδ protein is expressed in normal breast epithelial cells and in low-grade cancers. C/EBPδ protein (but not mRNA) expression correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
4
23
0
1
Order By: Relevance
“…It may be argued that chemical inhibitors are non-specific and the effect may not be attributed to a specific gene, however, knockdown of SNAI2 using siRNA transfection resulted in marked reduction in cell growth in TamR cell lines similar to the chemical inhibitors, confirming the importance of the genes in endocrine resistance. In agreement with this, a recent report showed that reduced expression of SNAI2 reduces the aggressiveness of cancer cells [ 33 ].…”
Section: Discussionsupporting
confidence: 83%
“…It may be argued that chemical inhibitors are non-specific and the effect may not be attributed to a specific gene, however, knockdown of SNAI2 using siRNA transfection resulted in marked reduction in cell growth in TamR cell lines similar to the chemical inhibitors, confirming the importance of the genes in endocrine resistance. In agreement with this, a recent report showed that reduced expression of SNAI2 reduces the aggressiveness of cancer cells [ 33 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, C/EBPδ is involved in the regulation of pro-apoptotic gene expression and growth arrest during mammary gland involution [ 19 , 20 ]. In line with these data, C/EBPδ indeed acts as a tumor suppressor in breast cancer [ 21 , 22 , 23 ], ovarian serous carcinoma [ 24 ], cervical carcinoma [ 25 ], leukemia [ 26 ] and hepatocellular carcinoma [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 60%
“…C/EBPδ has been found to negatively affect tumor growth by inducing growth arrest and differentiation [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Recently, however, C/EBPδ was also suggested to drive tumor progression and/or metastasis in certain tumor types [ 29 , 30 , 31 , 32 ], suggesting that C/EBPδ may either suppress or promote tumor progression in a context specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that abundant C/EBPδ expression is associated with estrogen receptor (ER)+ BC and low tumor grade, and that C/EBPδ attenuates proliferation and motility of ER+ MCF-7 cells in culture 27 . When assessed in vivo, however, CEBPD -silenced MCF-7 tumors grew significantly more slowly than controls and mice therefore survived longer (Fig.…”
Section: Resultsmentioning
confidence: 99%